Pendidikan Islam Di Madrasah: Sejarah dan Kontribusinya - Alawiyah Nabila; Muhammad Zuhdi Hibatullah; Eko Nursalim; Hasan Hasan (STIT Syekh Muhammad Nafis Tabalong, 2022)
Pendidikan as a process of lifelong learning. Education plays a crucial role in preparing people for today's world because it can change the way the general public thinks about a variety of issues. Many people view education as a foundation for improving and developing human character and morality. Madrasah is one of the important Islamic educational institutions with the mission of preparing the next generation of Muslims to build mosques and bangsas in the distant past. This article is written using an appropriate citation style based on existing procedures and a variety of source materials, including relevant research articles, books, journals, and study results. The presence of Islamic education in madrasas is expected to enhance and strengthen students' keimanan through education and experience of Islamic subjects, making Muslims more resilient and self-assured.